Accuracy and repeatability of the Polar® RS800sd to evaluate stride rate and running speed - Hausswirth, C.; Le Meur, Y.; Couturier, A.; Bernard, T.; Brisswalter, J. (International Journal of Sports Medicine, 2009)
The purpose of this study was to evaluate the accuracy and the repeatability of a new running computer system (RS800sd, Polar®, Kempele, Finland) which included the measurement of running speed (RS) and stride rate (SR). Eight well-trained triathletes participated in this study. First, they completed an incremental continuous maximum test on a treadmill (from 12 km.h-1 to 18 km.h-1) at 0% grade. Then the subjects took part in a second test to determine RS800sd intra-reproducibility to evaluate running speed. They ran twice during 5 min at a pace corresponding to their maximal lactate steady-state. During these two tests, RS and SR were recorded by the RS800sd system, by an optical sensor system (for RS) and a force-sensitive device (for SR). No difference was found between the RS800sd system and the reference systems both for RS (ICC=0.95) and SR (ICC=0.69). Moreover RS measures were statistically repeatable. This study provided evidence for the validity of the RS800sd system for measuring the kinematic characteristics of running (speed and frequency). Further investigations are needed to replicate these findings at lower running speeds, notably during walking to assess its capacity to evaluate physical activity in natural conditions.